Gender Dimensions of Small-Scale Cross-Border Trade in Cambodia and the Lao People’s Democratic Republic - World Bank Group (World Bank, Washington, DC, 2016)
The findings presented here, from a World Bank study led by the Trade and Competitiveness Practice of the World Bank, fill the gap in our knowledge about the patterns of small-scale cross-border trade in Cambodia and Lao PDR and those engaged in it. This knowledge will help inform future investments in trade integration and identify how interventions might be adjusted to ensure that vulnerable border users are able to realize the benefits of trade modernization. Given the lack of data on small-scale cross-border trade and traders, an innovative mix of survey strategies was implemented in Poipet and Bavet, Cambodia (on the borders with Thailand and Vietnam, respectively), and in Vangtao, Lao PDR (bordering Thailand). The three border crossings were chosen based on field observations and qualitative interviews in the vicinity of more than ten different border checkpoints. Selection criteria included trade volume, diversity and representativeness of trade patterns, and the active involvement of Lao and Cambodian citizens. Cambodia and Lao PDR were selected because they are the poorest of the four countries. Qualitative data from field observations, stakeholder interviews, and focus group discussions were combined with quantitative measures (sampling frames listing small-scale cross-border trade transactions and in-depth interviews) to provide a clear and accurate picture of small-scale cross-border trade and its practitioners.